A Robotic Communication Middleware Combining High Performance and High Reliability - Liu, Wei; Wu, Hao; Jiang, Ziyue; Gong, Yifan; Jin, Jiangming (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
With the significant advances of AI technology, intelligent robotic systems have achieved remarkable development and profound effects. To enable massive data transmissionin an efficient and reliable way, both high performance andhigh reliability should be taken into account in system design. However, the conventional communication middleware used in the majority of autonomous robotic systems, is based on socked-based methods, which always lead to high latency. Moreover, some sophisticated communication middleware utilizes shared memory upon ring buffers for high performance without consideration of the reliability. To obtain both high performance and high reliability, we employ shared memory for performance improvement and propose a novel socket-based communication control algorithm to improve reliability during data transmission. Furthermore, based on the proposed algorithm, we implement a novel robotic communication middleware, named Robust-Z, combining both high performance and high reliability. Experimental results show that (1) Robust-Z is able to gain up to 41% and 5% performance improvement compared to ROS2 and Apollo CyberRT, respectively; (2) Robust-Z is able to provide crash safety and reduce 5.2% data missing rate compared with CyberRT.